Reorganization of the system of intra-holding settlements: Methodological tools, efficiency assessment - Yu. V. Nemtseva; A. V. Bekker (Финансы: теория и практика)
In the context of growth trends in the scale and diversification of business, the internal costs of companies with a complex holding structure are also increasing. Solutions that improve the efficiency of settlement systems are particularly relevant and significant. Therefore, the paper is devoted to the problems of building settlement systems that minimize the negative impact of certain factors reducing the economic efficiency of calculations. The purpose of the study is to develop methodological foundations for rationalization the holding’s settlement system based on clearing obligations. The tasks of this paper are set as follows: to propose methodological tools for the reorganization of the system of intra-holding settlements; to test the proposed recommendations for the rationalization of the settlement system in holding structures. According to the results of the study, the authors systematized a set of factors that determine the effectiveness of the system of intra-group settlements. It is proposed to attribute the number of payment transactions and the volume of payment turnover to the quantitative factors of the settlement system efficiency. Qualitative factors of the settlement system efficiency are associated with the consolidation of financial information, the degree of automation of settlement processes, and the flexibility of the settlement system. The authors used the Ward method to build a cluster structure of the holding based on the analysis of payment turnover of pairs of companies, statistical methods of quantitative and qualitative assessment of the effectiveness of the holding’s settlement system. The scientific novelty is expressed by the fact that the paper offers methodological tools for reorganization the system of intra-holding settlements. A methodology for rationalization the holding’s settlement system based on clearing obligations, universal in use by holding-type companies, has been developed and its approbation has been carried out. The conclusions based on the results of the study form recommendations for changing some aspects of the holding’s activities in accordance with the results of the modernization of the holding’s settlement system. The method of rationalization of the system of intra-holding settlements proposed by the authors has versatility in application and can be used in solving management tasks within any holding.